Lift Force Analysis on Australian Aboriginal Boomerang of Several Design Variations Parameters - Mohd Firdaus B Sapidih, Mohd Firdaus (2009)

(untitled)
The objective of this research is to analyze lift force of Australian Aboriginal boomerang and few other designs based on several design parameters which are variation of area and angle between blades.